PENGARUH PROFITABILITAS, TRANSFER PRICING, DAN MANAJEMEN LABA TERHADAP TAX AVOIDANCE - Renal Ijlal Alfarizi (2021)
This research is a quantitative study which aims to determine the effect of profitability, transfer pricing, and earnings management on tax avoidance. The population in this study are mining companies listed on the Indonesia Stock Exchange for the period 2016-2019. This study used 9 mining companies listed on Indonesia Stock Exchange in 2016-2019 as a sample prepared based on purposive sampling technique. Testing in this study using the Home Linear Regression Analysis technique with the Spss program and a significance level of 5%. The results obtained from the research (1) there is no significant effect between profitability on tax avoidance, (2) there is a positive and significant effect between transfer pricing on tax avoidance, (3) there is no significant effect between earnings management on tax avoidance.